How should Bad Schwartau develop its innovation capabilities to sustain competitive advantage in the German food production market? - von Ludowig, Philipp (2010)
The study starts with an explanation of ‘innovation’ and its significance for business organizations, followed by a description of Bad Schwartau, the company of investigation; its market environments, competitors and its current product portfolio. The next chapter contains an explication of the five dimensions of innovation (Tidd & Bessant, 2009), what these dimensions cover and why they are a useful approach for the investigation. Two methods have been chosen for the further research, an innovation self assessment survey and a qualitative interview research. The results of the self assessment lead to a ranking of the five dimensions; this gives a first indication about the innovation capabilities of the firm. The second method is a qualitative interview research; it analyzes relevant issues in depth. All content and results of the interviews have been categorized. The core findings are separated in strength and weaknesses. Based on that, areas for improvement have been determined. The research study ends with a set of recommendations, how Bad Schwartau should improve and develop its innovation capabilities.